Principal's Academic Supervision Management in Improving The Professional Competence of Elementary School Teachers - Sri Astuti; Suharyanto H. Soro (CV. Media Digital Publikasi Indonesia, 2025)
The management of academic supervision by school principals, aimed at improving the professional competence of elementary school teachers, is a significant factor contributing to the decline in the quality of learning. Therefore, the existence of management plays an important role in maximizing the potential of teachers so that it has a positive impact on the quality of learning. Academic vision is one of the competencies of school principals, focusing on creating the quality of educational units so as to achieve superior accreditation. The management of academic supervision of the principal includes planning, organizing, implementing, and control/supervision. The purpose of this study is to find out the management of academic supervision of school principals in improving the professional competence of elementary school teachers. This research uses a case study approach. The data collection methods used are observation, interview, and documentation methods with school principals and teachers as informants. The data collection is aimed at answering research problems. The selection of respondents was carried out by purposive sampling. The results of the study showed: (a) Planning for academic supervision of school principals includes the preparation of supervision programs and the creation of supervision instruments, and (b) implementation of supervision using the directive approach, PMM application, and individual and group techniques. (c) Supervision and supervision evaluation include monitoring, preparation of follow-up plans, and reporting. (d) Supporting factors for supervision are the existence of adequate resources, while factors that inhibit supervision include limited understanding of the importance of academic supervision and management of school principals. The conclusion of the results of this study shows that the management of the supervision of the principal has a positive impact on improving the professional competence of teachers of SDN Sedaratu and SDN Sukajadi.